Endodontic Management of an Infected Primary Molar in a Child with Agenesis of the Permanent Premolar - Asgary, Saeed; Fazlyab, Mahta (Iranian Endodontic Journal, 2016)
Missing of mandibular second premolar is one of the most common types of tooth agenesis. In such cases, maintenance of the primary second molar, if possible at all, can prevent many treatment procedures in future. The present case report represents the endodontic management of a necrotic left mandibular primary second molar that had developed an abscess. Considering the missing of the permanent successor, the tooth was disinfected during endodontic preparation and the root canal system was filled with calcium-enriched mixture (CEM) cement in the same session. After 12 months of regular follow-up, not only the tooth was functional and symptom-free, but also healing of the inter-radicular bone lesion and re-establishment of the lamina dura was indicative of treatment success. Further trials are suggested to confirm CEM biomaterial use for management of infected primary molars associated with endodontic lesion. Keywords: Calcium-Enriched Mixture, CEM cement, Endodontic, Primary Molar, Tooth Agenesis, Tooth Missing